Low-Rank and Joint Sparse Representations for Multi-Modal Recognition - Zhang, Heng (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2017)
We propose multi-task and multivariate methods for multi-modal recognition based on low-rank and joint sparse representations. Our formulations can be viewed as generalized versions of multivariate low-rank and sparse regression, where sparse and low-rank representations across all modalities are imposed. One of our methods simultaneously couples information within different modalities by enforcing the common low-rank and joint sparse constraints among multi-modal observations. We also modify our formulations by including an occlusion term that is assumed to be sparse. The alternating direction method of multipliers is proposed to efficiently solve the resulting optimization problems. Extensive experiments on three publicly available multi-modal biometrics and object recognition data sets show that our methods compare favorably with other feature-level fusion methods